P Developed A Standard Instrument for Measuring The Skills of Teaching Elderly Brain Gymnastics for Nursing Students - Putra, Anggihsyah; Soegiyanto, Soegiyanto; Ridlo, Saiful (Universitas Negeri Semarang, 2018)
The current instrument has not been able to assess the skills of nursing students individually. The research aims to develop a standard instrument for measuring the elderly brain gymnastics teaching skills for nursing students that are valid and reliable. The method used is research development with 9 steps of development. Content validity of the instruments tested to three experts in the field, the construct validity, construct validity with Exploratory Factor Analysis (EFA), and reliability with CronbachAlpha. The results show the validity of the contents of 30 items having a value of ≥ 0.3 in a limited-scale instrument trial with a sample of 34 nursing students showing a percentage of the 87% readability test, which means a standard instrument for measuring the skills of teaching elderly brain gymnastics to eligible nursing students for used in large-scale trials. The KMO results in large-scale instrument testing in the field with the number of respondents 90 nursing students showing a value of 0.821, MSA> 0.5 and Bartlett's significance test of 0.000 this means the data is feasible for further analysis.The exploratory factor analysis show seven factors from 30 statement items. The value of factor is 0.3, which signify the whole item was valid. Based on the reliability test using Alpha Cronbach obtained value of 0.946 so that the instrument is reliable. The conclusions of the standard instrument for measuring the skills of teaching elderly brain gymnastics for nursing students developed were valid, reliable and feasible to be used. Benefits of the research is to provide information and thought contribution in an effort to improve the quality of nursing gerontik teaching during practicum activity of elderly brain gym exercises.